(P)rescription narratives : feminist medical fiction and the failure of American censorship - Tavera, Stephanie Peebles (Edinburgh University Press, 2022)
Examines how women writers of medical fiction rewrite cultural narratives of the female body against censorship under the Comstock Laws.
Keywords: American fiction -- Women authors -- History and criticism.; Medical fiction, American -- History and criticism.; Censorship -- United States -- History.; Disabilities in literature.; Women with disabilities in literature.; Women in literature.; Human body in literature.; Handicap dans la littérature.; Handicapées dans la littérature.; Femmes dans la littérature.; Corps humain dans la littérature.; LITERARY CRITICISM / Feminist.; American fiction -- Women authors; Censorship; Disabilities in literature; Human body in literature; Medical fiction, American; Women in literature; Women with disabilities in literature; United States; Literature: history & criticism.; Literary theory.; Literary studies: fiction, novelists & prose writers.; Feminism & feminist theory.; Literature.; Criticism, interpretation, etc.; History